Differences Between Alpha-Fetoprotein (AFP) and Prothrombin Induced by Vitamin K Absence or antagonist II (PIVKA-II) Values as Early Detection Method for Hepatocellular Carcinoma (HCC) and Cirrhosis - Bayu Eka Nugraha; Nugraha Setiawan; Hani Susianti; Bogi Pratomo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Background: Hepatocellular carcinoma is a common cancer worldwide and has a high mortality. Biomarkers could theoretically help to detect the disease at an earlier stage before symptoms occur and improve the treatment outcomes. The first biomarker found was AFP (not very accurate and 30-40% of HCC may be missed). PIVKA-II can be used as an early detection method to diagnose HCC.Method: A cross sectional study on in-patients or out-patients at Saiful Anwar Malang Hospital from July 2016 to October 2016.Results: The p value (p 0.05) obtained using Kolmogorov-Smirnov was 0.166 for diagnosis of HCC and 0.147 for the diagnosis of hepatic cirrhosis. The p value (p 0.05) obtained using Shapiro-Wilk was 0.103 for diagnosis of HCC and 0.087 for the diagnosis of cirrhosis. Comparative test using the LSD method showed PIVKA-II serum levels in HCC as compared to hepatic cirrhosis as significant with a p-value less than 0.05 (p 0.05), that is 0.025. However comparative test using the Tukey HSD method showed that the results obtained were not significant. According to the PIVKA-II cut off value, the sensitivity and specificity to detect cirrhosis and HCC was as large as 100%. According to the AFP cut off value, the sensitivity to detect cirrhosis and HCC was 93.3% and the specificity was 76.92%.Conclusion: Both PIVKA-II and AFP can be used to detect cirrhosis and HCC. However PIVKA-II exhibited better sensitivity and specificity in the detection of cirrhosis and HCC.